A Celebrity Endorsement as Global Marketing Strategy of LVMH Company Through Girl Group BLACKPINK in 2020-2024 - Putri, Ayuni Salsabila; Rasyidah, Resa (Cita konsultindo, 2024)
LVMH is an abbreviation for Louis Vuitton Moët Hennessy. Founded in 1987, this international luxury goods company is the biggest in the world, with its headquarters in Paris. Operating in more than 70 countries worldwide. LVMH’s business model is built on developing and acquiring high-end luxury brands that provide quality and exclusivity. Although LVMH brands dominate the luxury goods market independently, LVMH employs several marketing strategies, including celebrity endorsement. The explosion of the South Korean entertainment industry has made various Korean celebrities, including the girl group Blackpink, one of the largest girl groups in the world today, sought after for collaborations by LVMH. Consisting of four members, namely Jisoo, Jennie, Rose, and Lisa. All BLACKPINK members are celebrity endorsers for several brands under the LVMH company, such as Jisoo with Dior, Jennie with Gentle Monster, Rose with Tiffany & Co. and Rimowa, and Lisa with Celine, Bulgari, and Louis Vuitton. This shows that Blackpink impacts the brands that collaborate with them.